I derived demand, given a Cobb-Douglas utility function but I am not really sure if I did it correctly. I am especially struggling with the sum signs and the subscripts of $i$ & $j$. It would be really great if someone could check. I want to maximize utility for 2 goods, here $j$ and $i$.

$\ u(x_i)=\prod_{i=1}^n x^a_i $

$\ s.t.:M=\sum_{j=1}^n p_jx_j $

$\ L= \sum_{i=1}^n a_ilogx_i+\lambda(M-\sum_{j=1}^np_jx_j) $

$ (1)\frac{\partial L}{\partial x_i} = \frac{a_i}{ x_i}-\lambda p_i=0$

$ (2)\frac{\partial L}{\partial x_j} = \frac{a_j}{ x_j}-\lambda p_j=0$

$ (3)\frac{\partial L}{\partial \lambda} = M-\sum_{j=1}^np_jx_j=0$

from (1) and (2) it follows:

$ \frac{p_i}{x_i} = \frac{a_i/x_i}{a_j/x_j}=\frac{a_ix_j}{a_jx_i}$

$ x_j = \frac{p_ja_jx_i}{p_ja_j}$

$ x_j$ into (3)

$ M = \sum_{j=1}^np_j(\frac{p_ja_jx_i}{p_j/a_j})=0$

$ x_i= \frac{a_iM}{\sum_{j=1}^na_jp_j}$

Furthermore I would like to interpret what happens if we have an efficency shock for good $i$. Meaning, good $i$ becomes cheaper. This leads to an increase in relative income. So $M$ increases which leads to an increased demand for good $x_i$, rest hold constant. Is that correct?

  • $\begingroup$ Sorry. Yes, a drop in $p_i$. And of course $M$ stays constant, but normally we say then that the relative income increases, since the household spends less money for each unit of $x_i$. So again, $p_i$ drops, this will increase the amount of $x_i$. $\endgroup$
    – Pete
    Mar 15, 2019 at 16:59
  • $\begingroup$ His derivation is incorrect (due to a few algebra mistakes). The Cobb-Douglas utility function leads to a set of demand functions in which demand for each good depends only on it's own price. Check the two-good case for reference. See my solution below. $\endgroup$
    – dlnB
    Mar 15, 2019 at 17:05
  • $\begingroup$ @dlnB: You're right. I misread $p_j$ in the denominator as $p_i$. $\endgroup$
    – Herr K.
    Mar 15, 2019 at 17:10

1 Answer 1


From (1) and (2) you get $$\frac{x_j}{x_i}=\frac{a_j p_i}{a_i p_j},$$ or equivalently, $$x_j =\frac{a_j p_i}{a_i p_j} x_i.$$ Substituting this into equation 3 for $j=2,...,n$ and $i=1$ (solving for the demand function for good 1) we get $$M=p_1x_1 + \sum_{j=2}^n p_j \frac{a_j p_1}{a_1 p_j} x_1$$ $$M=p_1x_1 + \sum_{j=2}^n \frac{a_j p_1}{a_1} x_1$$ $$M=p_1x_1 + \frac{p_1}{a_1} x_1\sum_{j=2}^n a_j $$ $$M=p_1x_1(1 + \frac{1}{a_1}\sum_{j=2}^n a_j). $$ Finally, solving for $x_1$ we get $$x_1^* = \frac{M}{p_1}(1+ \frac{\sum_{j=2}^n a_j}{a_1})^{-1}$$ $$x_1^* =\frac{a_1}{\sum_{j=1}^n a_j} \frac{M}{p_1}.$$

Analogously, $$x_i^*=\frac{a_i}{\sum_{j=1}^n a_j} \frac{M}{p_i},$$ for $i=1,...,n$.

As is always the case for demand functions derived from a Cobb-Douglas utility function, the consumer spends a constant share of income on each good. To see this, rearrange the previous equation to get $$p_ix_i^*=\frac{a_i}{\sum_{j=1}^n a_j} M,$$ for $i=1,...,n$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.